Perbandingan Pengaturan Percobaan (Poging) Tindak Pidana Antara KUHP Lama dan KUHP Baru - Fiba Demada (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Currently, the Draft Criminal Code has been passed into Law No. 1 Year 2023 on the Criminal Code during the plenary session of the House of Representatives, 6 December 2022. In the New Criminal Code, attempted criminal offence is also reformulated. This research aims to compare the regulation of attempted criminal offence between the Old and New Criminal Code. This research uses normative juridical method. This research found that the differences between the Old and New Criminal Code are: First, the definition of attempted criminal offence. Second, the criteria on the ‘commencement of execution’ of attempted criminal offence. Third, criminal sanctions. Fourth, the condition that the attempt is not criminalised after the perpetrator has commenced the execution. Fifth, the regulation of ‘qualified attempt’. Sixth, the requirements for attempted criminal offences that are not punishable. While the similarities are: First, both regulate the maximum imprisonment of fifteen years for attempted criminal offences whose principal criminal offence is punishable by death or life imprisonment. Second, both regulate that the additional punishment for attempted criminal offences is the same as the additional punishment for the main criminal offence.